Interaction of criminological research and public policy - Blumstein, Alfred (Journal of quantitative criminology, 1994)
We examine here some of the interactions of research and policy over the past several decades. The “rehabilitation period” was effectively terminated by nulleffect evaluations of various rehabilitation techniques. The “just deserts-utilitarian period” was fed by research estimates of the deterrent and incapacitative effects of criminal justice activities. The more recent “overt politicization period” saw the earlier attempt to bring rational and theory-based perspectives to policy development replaced by much stronger emphasis on political concerns. We explore possible ways to reestablish the research-policy connections.